FINE POSITIONING SYSTEM OF MACHINE PARTS - A.V. LITVIN; A.A. ZAKHAROV (Advanced Engineering Research)
Electric circuit of analog and digital units of fine positioning system of machine parts using the programmable microcontroller is presented. The instrumentation electric drive controlled with PIC16F877A microcontroller is designed. The device is equipped with the interpolation unit, the digital display and the matrix keyboard for parameters setting. Optical incremental encoders and hard multipliers of analogue signals are used for the fine positioning.